Relevansi Album “Menari dengan Bayangan” Karya Hindia dalam Nilai-Nilai Pendidikan Agama Islam - Atana Ahmil Nahdhiyah; Mohammad Asrori; M. Fahim Tharaba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Hindia's album “Menari dengan Bayangan” is a bridge between the values ​​of Islamic religious education and the younger generation in modern culture. This research analyzes the values ​​of Islamic religious education in the album and their relevance. Qualitative research methods with library research are used by collecting data through observation and documentation. The research results show that the album contains the values ​​of faith, worship and morals, in line with the teachings in the book “Nashaihul Ibad” by Imam Nawawi al-Bantani. This shows that music and religion can work together in educating and improving oneself.